Makam Datuk Tualang Poso: Sejarah dan Pemeliharaannya - Fajar, Riki; Achiriah, Achiriah; Muchsin, Kasron (Mahesa Research Center (PT. Mahesa Global Publishing), 2022)
This article discusses the history of Datuk Tualang Poso's tomb and its maintenance in Amplas Village, Percut Sei Tuan District, Deli Serdang Regency. The method used in this study is a qualitative descriptive analysis method using a historical approach. The data in this study were obtained through observation, interviews, literature study and documentation. The results showed that the tomb of Datuk Tualang Poso had existed since the 17thÂ century. Datuk Tualang Poso was the first cleric sent by the Aru Sultanate to spread Islam in Amplas Village. The people of Amplas Village consider the tomb of Datuk Tualang Poso to be a sacred and sacred place. Until now the tomb of Datuk Tualang Poso is still solid and intact. The local community strives to continue to maintain and preserve the tomb as a form and form of respect for Datuk Tualang Poso for his role in spreading Islam while he was alive.